Cognitive science : an introduction to the study of mind - Friedenberg, Jay (Sage Publications, 2006)
Throughout history, different fields of inquiry have attempted to understand the great mystery of mind and answer questions like: What is mind? How does it operate? What is consciousness? Only recently have these efforts in traditional and cutting edge disciplines become more united in their focus. Cognitive Science is the comprehensive result of the authors' drawing together of this work. Key features: -Includes numerous ancillaries to promote the book's effective use, a companion student website at www.sagepub.com//CSstudy featuring online student-friendly exercises, E-flash cards, and interactive quizzes; and an Instructors CD-ROM with a test bank, chapter outlines, PowerPoint slides, a sample syllabus, and ideas for student projects - After introducing a major perspective, an 'Evaluating' section discusses the strengths and weaknesses of that perspective 'Thought Balloons' in margins further encourage students to think critically about key concepts; - 'In-Depth' boxes elaborate on specific models, illustrating them in concrete terms, and 'Minds On' exercises help students to familiarize themselves with key concepts in a hands-on fashion; - Student study is assisted via key terms (which are boldfaced and defined in context when first introduced), suggestions for further reading, and end-of-chapter 'Food for Thought' discussion questions; - Covers all the traditional concerns of cognitive science together with analysis of newer areas such as robotics and the evolutionary approach. Cognitive Science is the perfect introductory textbook for cross-disciplinary courses on the mind in psychology, linguistics, philosophy, and computer science.